Mutirão habitacional autogestionário: experiência do CAAP - grande São Paulo - 1980 e 1990 - Vaz, Ana Luiza de Lyra (2000)
This dissertation is about the origin and consolidation of the self-management approach in the building task-forces of São Paulo, analysing the evolution of the relationship between the State and the society in the struggle of the popular building movements to achieve an urban and building policy with social characteristics in the metropolitan area of São Paulo in the 1980s and 1990s. It is based on the pratice of technical consultancy of the CAAP (Centro de Assessoria a Autogestão Popular), a non-governmental organization, rebuilding its history and clarifying its political and technical approach and the methodology developed there. After studying the historical and theoretical basis of self-management and analysing, within its own context, the experience of the Uruguayan Cooperativas Habitacionais por Ajuda Mutua, which inspired the practices which are the target of investigation in this study, the research traces step by step the evolution of the idea of self-management in the solution of the housing problem for the low-income population and how this self-management practice contributes for the self-perception of the participants of this movement as history agents. Starting with the relationship between the CAAP and the Associações de Construção Comunitária and the União de Movimentos de Moradia-SP, the study develops the methodology used in all phases of the self-managed entreprenencial process, with an emphasis on social work. The political, technical and social factors that formed the self-management approach are analysed, starting from the pilot projects in the ABC area and in the south of São Paulo that led to the development of a public policy at both city and state level. This study is based on documents kept at the CAAP, on written and oral memories of the , subjects involved and on the consultancy practice of the author with the popular movements. Finally, the study arrives at the conclusion that the collective work in the self-managed task-force contributes to the consolidation of citizenship, providing a new view of the relationship between the public and the private that the popular housing movements acquire as political subjects